Standardized Electrolyte Supplementation and Fluid Management Improves Survival During Amphotericin Therapy for Cryptococcal Meningitis in Resource-Limited Settings. (25th August 2014) - Bahr, Nathan C.; Rolfes, Melissa A.; Musubire, Abdu; Nabeta, Henry; Williams, Darlisha A.; Rhein, Joshua; Kambugu, Andrew; Meya, David B.; Boulware, David R.
Abstract : Standard electrolyte monitoring and supplementation as compared to sporadic electrolyte monitoring and replacement improves mortality. Abstract: Background. Amphotericin B is the preferred treatment for cryptococcal meningitis, but it has cumulative severe side effects, including nephrotoxicity, hypokalemia, and hypomagnesemia. Amphotericin-induced severe hypokalemia may predispose the patient to cardiac arrhythmias and death, and there is very little data available regarding these toxicities in resource-limited settings. We hypothesized that standardized electrolyte management during amphotericin therapy is essential to minimize toxicity and optimize survival in sub-Saharan Africa. Methods. Human immunodeficiency virus-infected, antiretroviral therapy naive adults with cryptococcal meningitis were prospectively enrolled at Mulago Hospital in Kampala, Uganda in 3 sequential cohorts with amphotericin B deoxycholate induction treatment. Intravenous fluid use was intermittent in 2001–2002, and universal in 2006–2012. In 2001–2009, serum potassium (K + ) was monitored on days 1, 7, and 14 of treatment with replacement (K +, Mg 2+ ) per clinician discretion. In 2011–2012, K + was measured on days 1, 5, and approximately every 48 hours thereafter with universal electrolyte (K +, Mg 2+ ) supplementation and standardized replacement. Clinical outcomes were retrospectively compared between fluid and electrolyte management strategies. Results. With limited intravenous fluids, the 14-day survival was 49% in 2001–2002. With universal intravenous fluids, the 30-day survival improved to 62% in 2006–2010 ( P = .003). In 2011–2012, with universal supplementation of fluids and electrolytes, 30-day cumulative survival improved to 78% ( P = .021 vs 2006–2010 cohort). The cumulative incidence of severe hypokalemia (<2.5 mEq/L) decreased from 38% in 2010 to 8.5% in 2011–2012 with universal supplementation ( P < .001). Conclusions. Improved survival was seen in a resource-limited setting with proactive fluid and electrolyte management (K +, Mg 2+ ), as part of comprehensive amphotericin-based cryptococcal therapy.